Downstream processing of extracellular phytase from aspergillus niger: chromatography process vs. aqueous two phase extraction for its simultaneous partitioning and purification - Bhavsar, Kavita P.; Kumar, V. Ravi; Khire, Jayant Malhar (Process Biochemistry, 2012)
The application of single step aqueous two-phase extraction (ATPE) for the downstream processing of phytase from Aspergillus niger NCIM 563, produced under solid state fermentation, has been studied and compared with the traditional multi-step procedure involving salt precipitation and column chromatography. High phytase recovery (98.5%) within a short time (3 h) and improved thermostability was attained by ATPE in comparison to 20% recovery in 96 h by chromatography process.The ATPE method, therefore, seems to be an interesting alternative for simultaneous partitioning and purification of phytase. The influence of system parameters; such as, phase forming salts, polymer molecular weight and system pH on the partitioning behavior of phytase was evaluated. The ATPE system consisting of combination of polyethylene glycol (PEG) 6000 and 8000(10.5%) and sodium citrate (20.5%) resulted in one-sided partitioning of phytase in bottom phase with a purification factor of 2.5. This is the first report on phytase purification using liquid-liquid extraction and the results are likely to be beneficial in the poultry feed industry. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Aspergillus niger; liquid-liquid extraction; Phytase; Polyethylene glycol; Purification